Chitosan oligosaccharide/silica nanoparticles hybrid porous gel for mercury adsorption and detection. (September 2021) - El Kurdi, Riham; Chebl, Mazhar; Sillanpää, Mika; El-Rassy, Houssam; Patra, Digambara
Abstract: Hybrid porous gel has successfully been prepared in situ by interaction of silica nanoparticles with chitosan oligosaccharide lactate. The concentration of silica nanoparticle is crucial for the formation of the gel. Water remediation using this material was explored where the hybrid gel was used as adsorbent for mercury ions from aqueous media and the metal ion removal was investigated under different conditions. Moreover, the detection of mercury ions was performed using emission fluorescence spectroscopy in the presence of a specific fluorophore molecule, such as curcumin. Adding mercury ions was followed by the penetration of curcumin into the hydrophobic pocket of chitosan oligosaccharide lactate, boosting thereby the emission intensity. In addition, the selectivity towards mercury was studied. The elaborated technique was found to be selective, simple and fast with low limit of detection value. Graphical Abstract: ga1 Highlights: Hybrid Silica-COL was synthesized from silica nanoparticles and chitosan oligosaccharide lactate. Silica-COL is highly selective towards mercury ion removal from aqueous media. The efficiency of Silica-COL in adsorbing mercury ions was studied. Silica-COL-Curcumin is a potential detector of mercury ions in aqueous environments.